Promoting HOTS and critical thinking to English students of higher education through authentic assessment - Lilis Lisdawati; Amalul Umam (Erudita: Journal of English Language Teaching, 2022)
The development of social life relationship in this 21st century becomes more challenging than the previous era. All the human being needs to be designed sophisticatedly with some skills to maintain the global welfare, such as critical thinking skill which is the ability to test, analyze and explain the validity of the information according to a particular task or situation. Critical thinking that is accompanied by creativity build a high terminology called higher order thinking skills (hereafter, HOTS) that produces the activity of analyzing, evaluating and creating something new. Critical Thinking and HOTS are expected to be implemented in Indonesia’s educational policies due to critical thinking skill in Indonesia is still low. Therefore, this study aims to know the role of authentic assessment on higher education English students’ critical thinking skill and HOTS. This study used qualitative descriptive approach by giving participants a bunch of discussion in a form of interview where the participants were four college students from a private university in Bogor. The result of this study showed that authentic assessment promotes English students’ critical thinking and HOTS through the activity where they were able to explore and reflect their comprehension to their situation and make a product related to their learning.